Calculation of thermodynamic properties of liquid Fe-Ln alloys - Kotova, Natalia Vladimirovna; Golovata, Natalia Valerievna; Usenko, Natalia Igorevna (Київський національний університет імені Тараса Шевченка, 2015)
This paper presents the results of estimation of thermodynamic properties of binary Fe–Ln systems which characterized by small or moderate energy of component interaction in liquid state. The good agreement between enthalpies of mixing calculated in “surrounded atom” approximation and experimentally obtained enthalpies of mixing is observed for all investigated systems including Fe–Pr one, in which sign variable values of heat effects were determined. The method of estimation of excess Gibbs energies of liquid Fe–Ln alloys is proposed and the results of such estimation are given for a number of systems including those experimentally unexplored yet.
Keywords: liquid alloys; iron; lanthanides; thermodynamic properties calculation; “surrounded atom” model